Measuring Performance of Non Government Organizations: A Comparative Study of AMDA Nepal and General Welfare Pratisthan (GWP) - Thapa, Sangita (JMC Research Journal, 2019)
The number of NGOs has grown significantly over the past several years which shows significant development. The NGOs have been contributing in the different sectors of life like health, education, environment, agriculture, inclusion, social justice, democracy, good governance and many more in collaboration with different partners in local, national and global level. So their work is diverse and complex in nature. NGOs are formed for social reform and citizen's awareness. NGOs wish to address their stakeholder's desire through the operational performances. NGOs can't afford to limit their role into a single sector because they work with the people and for the people. The performance of NGOs play vital role in discharging the accountability placed on them and to meet the expectation of the stakeholders. Therefore, performance of NGOs is key satisfier to the interest of the different stake holders and society at large. There are many factors that contribute in the organizational performance. To measure the organizational performance, independent variables like quality orientation, work climate, employee satisfaction, growth and relationship, organizational strategies and organizational diagnosis are useful. Some demographic variables such as age, gender, education and work experience are also considered as moderating variables. This has provided the status of performance and correlation between the variables. Therefore, it is beneficial to understand these internal variables so that management can take appropriate action to improve the performance.